2022
DOI: 10.1021/acsami.2c05485
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the ReS2 Interlayer Promises High-Performance Potassium-Ion Storage

Abstract: Improving the electrochemical kinetics and the intrinsic poor conductivity of transition metal dichalcogenide (TMD) electrodes is meaningful for developing next-generation energy storage systems. As one of the most promising TMD anode materials, ReS2 shows attractive performance in potassium-ion batteries (PIBs). To overcome the poor kinetic ion diffusion and limited cycling stability of the ReS2-based electrode, herein, the interlayer distance expanding strategy was employed, and reduced graphene oxide (rGO) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…The enlarged lattice spacing is believed to be beneficial for K + insertion and extraction. [31,32] In addition, we conduct a fast Fourier transition (FFT) on the HRTEM image, and the (001), (100), and (110) planes are observed (Figure 1j), [22,23] once more implying that the plasma treatment does not destroy the main crystal structure of VSe 2 . Moreover, many lattice distortions are found in the inverse FFT (IFFT) HRTEM image of P-VSe 2−x (Figure 1k), whereas they are almost invisible in the case of VSe 2 (Figure S4b, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The enlarged lattice spacing is believed to be beneficial for K + insertion and extraction. [31,32] In addition, we conduct a fast Fourier transition (FFT) on the HRTEM image, and the (001), (100), and (110) planes are observed (Figure 1j), [22,23] once more implying that the plasma treatment does not destroy the main crystal structure of VSe 2 . Moreover, many lattice distortions are found in the inverse FFT (IFFT) HRTEM image of P-VSe 2−x (Figure 1k), whereas they are almost invisible in the case of VSe 2 (Figure S4b, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The interlayer expansion is probably attributed to lattice distortion coupled with the extremely weak interlayer coupling. 19,22 The enlarged interlayer spacing could reduce the Na + diffusion barrier and promote fast Na + insertion/extraction, thus contributing to the acceleration of the electrochemical reaction kinetics of SIBs. 5,37 Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13][14][15] As an emerging representative material of layered transition metal dichalcogenides (LTMDs), rhenium disulfide (ReS 2 ) has recently attracted increasing attention in various application fields such as electrocatalysis, electrochemical energy storage, optoelectronics, etc. [16][17][18][19] The layered structure with a large interlayer spacing of 0.61 nm and extremely weak interlayer van der Waals (vdWs) interactions (18 meV for ReS 2 vs. 460 meV for MoS 2 ) makes it highly suitable for alkali-ion batteries, especially for storage of Na-ions that have large ion sizes. [20][21][22][23] ReS 2 has a theoretical specific capacity of 428 mA h g −1 for sodium storage with intercalation coupled with a conversion mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a previously reported systematic study demonstrated the better LIB performance of ReS 2 than that of MoS 2. These good features make ReS 2 a competitive material in the energy storage field. Nevertheless, the rapid capacity fading performance has hindered the applications of ReS 2 anodes.…”
Section: Introductionmentioning
confidence: 99%